Physical Fitness Profiles Among a Women Hockey Team Preparing for Sukan Malaysia 2018 - Md Nadzalan, Ali; Low Fook Lee, Jeffrey; Mohd Rasyid, Nelfianty (International Journal of Engineering and Technology, 2018)
The purpose of this study is to analyse the physical fitness of a womenâ€™ hockey team preparing for the 2018 Sukan Malaysia (SUKMA) Games. Players representing a state were recruited as participant of this study and were tested on their muscular strength, muscular endurance, power, flexibility, speed and agility ability. Descriptive statistics were used to measure the mean and standard deviation of each physical characteristics and data scores. Repeated measure analysis of variances (ANOVA) were used to compare the muscular strength, muscular endurance, flexibility, speed, power and agility ability between each period of data collection. Results showed only sit and reach and agility tests showed significant differences between the two phases of data collection. Sit and reach test score was found to be decreased during the second phase of data collection, thus is worrying. Agility t-test score showed significant improvement during the second phase of study. No significant differences were found for the other variables. It can be seen in this study that the majority of players did not able to obtain great score in many fitness components (i.e. muscular strength, agility, flexibility, power and speed). These data stress the importance of rigorous pre-season conditioning programs consisting of resistance training and plyometric exercises, and game play to maximize in-season physical abilities among hockey players.Â Â